Histone code of genes induced by co-treatment with a glucocorticoid hormone agonist and a p44/42 MAPK inhibitor in human small intestinal Caco-2 cells - Inamochi, Yuko; Mochizuki, Kazuki; Goda, Toshinao (Biochimica et biophysica acta, 2014)
Inactivation of glucocorticoid hormones and p44/42 mitogen-activated protein kinase (MAPK) is thought to be important in small intestinal maturation and expression of genes related to intestinal differentiation and functions. We investigated target genes induced by co-treatment for 48h with a glucocorticoid hormone agonist, dexamethasone (Dex), and a p44/42 MAPK inhibitor, PD98059 (PD), in a small intestine-like cell line (Caco-2) using microarray analysis. We also investigated whether expression changes of the target genes induced by the co-treatment are associated with histone modifications around these genes. Co-treatment of Caco-2 cells with Dex and PD enhanced several genes related to intestinal differentiation and functions such as SCNN1A, FXYD3, LCT and LOX. Induction of the SCNN1A gene was associated with increased presence of acetylated histone H3 and H4 and di-methylated histone H3 at lysine (K) 4 around the transcribed region of the gene, and induction of the FXYD3 gene was associated with increased presence of acetylated histones H3 and H4 from the promoter/enhancer to the transcribed region of the gene. Induction of LCT and LOX genes was associated with increased presence of acetylated histone H4 on the promoter/enhancer region of the genes. Histone acetylation and/or histone H3 K4 methylation around the promoter/enhancer or/and transcribed regions of target genes are associated with induction of the genes by co-treatment with Dex and PD in Caco-2 cells. The histone code is specific to each gene with respect to induction by glucocorticoid hormone and inhibition of p44/42 MAPK in Caco-2 cells. •Glucocorticoid hormone and inhibition of p44/42 MAPK coordinately induce intestinal gene expression.•Glucocorticoid hormone and inhibition of p44/42 MAPK differentially enhance histone modifications.•Histone modifications are enhanced in transcribed and promoter/enhancer regions.